Rizki Aulia Rahman Natakusumah’s Leadership in the Pandeglang Regency Road Program (Jakamantul) - Romli, Ombi; Albar, Fikri Anidzar (Lenggogeni Data Publishing, 2025)
This research aims to analyze the leadership of Rizki Aulia Rahman Natakusumah in implementing the “Jalan Kabupaten Mantap Betul” (Jakamantul) program initiated by the Pandeglang Regency Government to improve the quality of regional road infrastructure. The study focuses on leadership style, implementation strategy, and the supporting and inhibiting factors affecting the program’s success. This research employs a descriptive qualitative approach with data obtained through in-depth interviews, literature review, and documentation. Informants include local government officials, program implementers, and beneficiary communities. The findings indicate that Rizki Aulia Rahman Natakusumah practices participatory and collaborative leadership, emphasizing open communication, staff empowerment, and community involvement. Such leadership strengthened institutional coordination, accelerated infrastructure implementation, and enhanced public trust in government performance. However, challenges remain, including limited budgets and field constraints that affect project completion targets. Overall, his leadership has proven effective in promoting public service innovation in infrastructure management by prioritizing transparency, collaboration, and social responsibility in responding to the needs of the Pandeglang community.